Phytochemical screening and antimicrobial activities of annona muricata leaves extract / Mohamad Fais Nordin - Nordin, Mohamad Fais (Faculty of Applied Sciences, 2017)
Annona muricata or which commonly known as soursop is from the family Annonaceae and it is used globally as a traditional medicine to heal small wound and disease cause by pathogens. The fruits, seeds, barks, leaves, and even roots have been used to treat external and internal infection, coughs, liver ailments, inflammation, diabetes, and extractions from the leaves have been widely used to kill pest. This study was conducted to determine the phytochemical constituent present in Annona muricata using methanol and hexane solvent and to determine antimicrobial property against Gram positive and Gram negative bacteria. Methanol showed the highest percentage yield of crude extract with 8.38% and for hexane only 0.26%. Phytochemical screening test was done with the methanol extract showed the presence of alkaloids, flavonoids, saponins, and tannins. Meanwhile for hexane extract showed the presence of saponins and tannins only. Methanol and hexane extracts were used against four types of bacteria species which are Staphylococcus aureus, Bacillus subtilis, Klebsiella pneumoniae and Pseudomonas aeruginosa. The antimicrobial activities were tested using four different concentrations of extracts; 25 mg/ml, 50 mg/ml, 100 mg/ml and 200 mg/ml to determine the inhibition zone of bacteria. Results showed that only methanol extract have antimicrobial property against Staphylococcus aureus, Bacillus subtilis, Klebsiella pneumoniae and Pseudomonas aeruginosa.